Development of Android Based Educational Games to Enhance Elementary School Student Interests in Learning Mathematics - Sarifah, Iva; Rohmaniar, Ai; Marini, Arita; Sagita, Julius; Nuraini, Sri; Safitri, Desy; Maksum, Arifin; Suntari, Yustia; Sudrajat, Ajat (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This research is an android-based educational game development research to increase interest in learning mathematics for elementary school students. This study aims to make the development of educational games able to be a solution in increasing students' interest in learning Mathematics at the initial level, namely the elementary school level. The method used in this research is the Research and Development model ADDIE (Analyse, Design, Development, Implement, Evaluation). In this study, it was limited to the implementation stage which was tested through experimental research. This research is included in the type of experimental research. The experimental design used is a simple experiment in the form of Posttest Only Control Group Design. The conclusion that can be drawn from this research is that Android-based educational games are proven to increase the interest in learning mathematics for elementary school students.